KONSEP REFORMASI BIROKRASI PELAYANAN PUBLIK DALAM PERSPEKTIF HUKUM KEPEGAWAIAN - adrie adrie (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2018)
To get a good government, bureaucratic reform is something that must be done from the beginning. Bureaucracy as a component of government must be returned to the functions, duties, and principles of public service. To develop public services that characterize good governance practice there are certainly many aspects that need to be addressed in the public bureaucracy. Writing of this scientific paper aims to know the concept of public service bureaucracy reform in the perspective of personnel law and to know the thinking of bureaucracy that can encourage good governance. Writing of this scientific paper using approach method that is normative juridical by way of researching library material which is secondary data and also referred [as] with research of library law. For data collection on the writing of this scientific paper, the author uses literature study techniques by reviewing data in the form of library materials by reading and studying literature books and legislation related to the issues discussed author. The conclusions of the writing of this scientific paper include: (1) The establishment of Regulation Number 5 of 2014 on the Civil State Apparatus enacted on January 15, 2014 which has brought new hope to accelerate the creation of a professional civil servants (ASN), free from political intervention, clean from corrupt practices, collusion and nepotism, able to provide public services for the community and able to perform the role as a glue of unity and national unity in order to achieve national goals; (2) Bureaucracy reform becomes an important part in realizing good governance. Bureaucracy reform is directed at efforts to prevent and accelerate the eradication of corruption in a sustainable manner, in creating good governance, clean governance, and free of KKN.